2007
DOI: 10.1242/jcs.03307
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial role for NFAT5 in both myoblast migration and differentiation during skeletal muscle myogenesis

Abstract: Skeletal muscle regeneration depends on myoblast migration, differentiation and myofiber formation. Isoforms of the nuclear factor of activated T cells (NFAT) family of transcription factors display nonredundant roles in skeletal muscle. NFAT5, a new isoform of NFAT, displays many differences from NFATc1-c4. Here, we examine the role of NFAT5 in myogenesis. NFAT5+/- mice displayed a defect in muscle regeneration with fewer myofibers formed at early times after injury. NFAT5 has a muscle-intrinsic function beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 81 publications
4
101
0
Order By: Relevance
“…14 Of the three NFAT5 targets involved in osmolyte accumulation we tested for this study, we found only AR to be present in substantial amounts in normal muscle, which confirms an earlier report 14 and points to a physiological role in muscle homeostasis. 15 Levels of TauT (The Human Protein Atlas: http://www.proteinatlas.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…14 Of the three NFAT5 targets involved in osmolyte accumulation we tested for this study, we found only AR to be present in substantial amounts in normal muscle, which confirms an earlier report 14 and points to a physiological role in muscle homeostasis. 15 Levels of TauT (The Human Protein Atlas: http://www.proteinatlas.…”
Section: Discussionsupporting
confidence: 81%
“…The relationship between NFAT5 and immune cell function has been put forward, and in macrophages, myo-inositol is believed to have a central role in cell volume regulation during phagocytosis. Infiltrating immune cells in murine muscle subjected to experimental muscle injury express NFAT5, 14 and SMIT protein levels have been shown to increase in liver macrophages subjected to hypertonic conditions. 40…”
Section: Smit Is Expressed In Muscle-infiltrating Immune Cellsmentioning
confidence: 99%
“…Indeed, it has been shown that NFAT5 is a transcriptional factor that stimulates cell migration (Jauliac et al, 2002;O'Connor et al, 2007). As expected, NFAT5 over-expression in MDA-MB-231 cells increased cell migration (Figure 2a), whereas NFAT5 depletion decreased it (Figure 2b).…”
Section: Resultssupporting
confidence: 71%
“…It will be interesting to test whether this ddx5/ddx17-dependent mechanism is involved in NFAT5 protein level regulation in hyperosmotic conditions. Similarly, NFAT5 protein level is regulated during development and NFAT5 has a role in muscle differentiation (O'Connor et al, 2007). As ddx5 and ddx17 also have a role in muscle differentiation (Caretti et al, 2006), it will be interesting to test the interplay between NFAT5 and ddx5/ddx17 in muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Five NFAT isoforms have been identified (16), and four isoforms (NFATc1, -c2, -c3, and -5) are expressed in skeletal muscle (17,18). NFATc1, -c2, -c3, and -5 have overlapping but also nonredundant functions in skeletal muscle, including control of myogenic differentiation, myoblast migration and fusion, and fiber type specification (18 -21).…”
mentioning
confidence: 99%